The cryosphere melt contribution to the imbalanced Asian Water Tower ... - Yu, Wusheng (Zenodo, 2024)
This repository includes the dataset associated to the following paper published in Nature 2024 XX: Tandong Yao, Lonnie Thompson, Wusheng Yu, et al., The cryosphere melt contribution to the imbalanced Asian Water Tower. ...